Cytotoxicity effect of Aaptamine and its derivatives on Acanthamoeba castellanii (IMR isolate) - Mat Amin, Nakisah; Hamdin, Muhammad Shafiq; Azarnudin, Muhd Amir Taufiq; Asari, Asnuzilawati; Abdul Rashid, Fatin Nur Ain; Mohd Nor, Siti Mariam (Publications International, 2018)
Acanthamoeba is a free-living amoebae that is ubiquitously present in various natural environments. In this study, several of Aaptamine derivatives (2-5) were synthesized and evaluated for their cytotoxicity effect against Acanthamoeba castellanii (IMR isolate). The Acanthamoeba viability was determine using range of concentration from 0 until 50 µg/mL for each compounds. The treatment was done for 72 hours and Eosin stainning was used to determine the cell viability. From the result obtained, Aaptamine (1) and its derivatives (2-5) have significant effect toward inhibition growth on Acanthamoeba with of 1,4-dibenzylaaptamine (5) was observed as the most potent compound as anti-amoeba agent.